2009
DOI: 10.1080/13676260903081632
|View full text |Cite
|
Sign up to set email alerts
|

Supporting young crime victims: discursive environments and formula narratives

Abstract: Within the crime victim movement and discourse on victimization, a novel victim category has been introduced: the young crime victim. This article analyses the professional discourse formed around the new notion, focusing on the needs of the young crime victim along with the practices, tools, and techniques used to deal with resistance at a support centre for young crime victims in Sweden. The institutional or professional discourse, which functions as an environment for the youths' stories about crime and vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Göteborg University's Sociology Department has produced a substantial amount of research in two main areas, economic crime (for example , Engdahl 2008;Larsson, 2003;Lindgren, 2002) and police-related research (Björk, 2005;Peterson, 2010;Wahlström, 2011), although studies have also focused on homelessness (Sahlin, 2004), violent crime, and crime victims and victim support (Hansen Löfstrand, 2009). Research in Göteborg is dominated by qualitative studies.…”
Section: Criminological Research In Swedenmentioning
confidence: 99%
“…Göteborg University's Sociology Department has produced a substantial amount of research in two main areas, economic crime (for example , Engdahl 2008;Larsson, 2003;Lindgren, 2002) and police-related research (Björk, 2005;Peterson, 2010;Wahlström, 2011), although studies have also focused on homelessness (Sahlin, 2004), violent crime, and crime victims and victim support (Hansen Löfstrand, 2009). Research in Göteborg is dominated by qualitative studies.…”
Section: Criminological Research In Swedenmentioning
confidence: 99%
“…Men in general have also been found to be less likely than women to seek help from professionals for different kinds of personal problems such as physical and psychosocial problems (Addis and Mahalik 2003) and are also often characterized in this way by others. Professional helpers also envisage young men who have been subjected to physical violence as not interested in talking about it and being difficult to reach emotionally (Burcar 2005 Hansen Löfstrand 2008Löfstrand , 2009Ryding 2005). Research also shows that men who show signs of being in a stressful situation, such as signs of being traumatised, are at risk of being evaluated more negatively and considered to have more severe problems than women with the same symptoms (O'Neil, Good and Holmes 1995;Robertson and Fitzgerald 1990;Seem and Johnson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous research has shown how victims of different types of crimes themselves understand their victimization and construct a victim narrative (cf. Åkerström et al, 2011; Burcar, 2005; Burcar and Åkerström, 2009; Fohring, 2018; Jägervi, 2014, 2016; Löfstrand, 2009a, 2009b). However, young people’s narrative constructions of victimhood, in relation to their need for community support, have not yet been explored in detail.…”
Section: Introductionmentioning
confidence: 99%